تمثـــلات الانتمـــــاء في الثقافــــة الشعبيــــة (El-Wahat Journal for Research and Studies, 2017)
Popular Culture Is One Of The Pillars Of The Concept Of Loyalty That Breeds And Grows Inside, By Selecting The Nature Of The Relationships That Bind Individuals To Each Other On One Side, And Their Relationship With The State On The Other Hand, In Addition To Determining The Nature Of Individual Responsibility Imposed By These Relationships. And Which Has Become More Distinct  In Many People Thoughts  And Their Feelings As Well As In  Their Practices And Aspirations Of Thinking, Values, Habits, And Beliefs And Even Wisdom With Which They Portrayed  The Realities Of Their Past And Their Future, What Contribtes Directly In The Construction And The Progress Of The  Society. Keywords -  Representations - Belonging- Popular - Culture